“Sekolah Ibu Program”: Women Resilience Program or Gender Blind Policy? - Mochamad Juniar Liyandi; Ika Arinia Indriyany; Luki Oka Prastio (Dealings Foundation Institute, 2024)
This article analyzes the Gender Blind Policy phenomenon in the “Sekolah Ibu Program” in Bogor City, Indonesia. This article aims to see whether there are gender gaps or inequality in the “Sekolah Ibu Program”. The “Sekolah Ibu Program” was created to reduce the divorce rate in Bogor City, Indonesia. The divorce trend in Bogor City has increased in the last three years. Therefore, the Bogor City government created a program to suppress divorce cases. In the “Sekolah Ibu Program”, there are learning modules such as parenting patterns, family health, family resilience, and others, so women are expected to have more knowledge about family resilience. The method used by the author in this research is Cresswell's qualitative case study approach. The author uses Naila Kabeer's Gender Blind Policy theory, which uses four indicators to determine the phenomenon in the program: participation, benefits, control, and access. These four indicators used to see the inequality and the gender gap in this program. The result shows that there is still a gender gap, such as what occurs in the “Sekolah Ibu Program”, where there are still limitations between women and their participation in the program.